(untitled) (Iranian Journal of Kidney Diseases, 2011)
Introduction. Both atorvastatin and mycophenolate mofetil (MMF) have been used for panel reactive antibodies (PRA) reduction in transplant candidates. The purpose of this study was to compare the effect of low-dose MMF and atorvastatin on PRA in sensitized hemodialysis patients waiting for kidney transplantation. Materials and Methods. A total of 40 adult patients with end-stage renal disease who were highly sensitized to human leukocyte antigens (PRA > 40%) were enrolled and randomly assigned into atorvastatin or low-dose MMF groups. All of the patients received the treatments for 2 months. The PRA status was determined at the end of the 1st and 2nd month. Results. Forty percent of the patients in the atorvastatin group compared with 5% in the low-dose MMF group showed complete response, defined as a minimum 50% reduction in PRA (P = .02). Reduction of PRA in the atorvastatin group was significantly higher than that in the low-dose MMF group (P = .01). No major infectious or other complications occurred in our patients. Conclusions. Atorvastatin has a significant effect on lowering of PRA in sensitized hemodialysis patients waiting for kidney transplantation. In addition, a short course of low-dose MMF is safe in ESRD patients; however, it has no effect on reduction of PRA.